Şazeliyye Tarikatının Derkaviyye Haşimiyye Kolu (Şam) - Morad, Abdullah (My University, 2021)
Tez, geçen yüzyılın başında Fas’tan Şam’a göç hareketiyle birlikte Şeyh Muhammed el-Haşimi’nin Şam’da başlattığı Şazeliyye tarikatının Şeyhi Muhammed Binyillis olan Darkaviyye kolunu ele almaktadır. Bu tezin değeri Şazeliyye Tarikatı Derkaviyye-Haşimiyye Kolunu tanımlayacı analitik bir yöntemle ele alınacak olmasında yatmaktadır. Tarihsel süreçleri inceleyerek, özellikle Fransa’nın Cezayir ve Suriye’yi işgali dönemlerinde, tarikatın toplumsal bağlamda kamuoyunu ve halkı bilinçlendirme konusundaki etkisini ortaya koyacaktır. Özellikle Osmanı Devleti’nin çöküşünden sonra başlayan Fransa ve İngiltere’nin işgali Şam’da oldukça zor koşullar oluşturdu. Bu zorluklar Suriye’nin bağımsızlığından sonra, yaşanan askeri darbeler, siyasi çatışmalar, Esed Baas Partisinin iktidara gelmesi ve sonunda 2011 yılında halkın ayaklanmasıyla birlikte artarak Tarikat sürdürülmeye devam etmektedir.

The concept of the thesis is about the studying of the (Darqwiya Tariqa) as a branch of (Shadhili Tariqa) which was created by (Sheikh Mohammed bin Yalis), reached us by (Sheikh Mohammed Al-Hashimi) and entered to Damascus through the Moroccan immigration at the onset of last century and spread throughout most of Damascus neighborhoods and districts. In this research, I will thoroughly work on getting answers to the following questions:How the Shadhili Hashemite Darqawiya Tariqa could spread in the city of Damascus and how could it take over the main part of the Damascus Sufism scene?Place of study: City of Damascus in the period from 1911 to 2015 AD (i.e., starting from the date of the arrival and entry of the Shadhili Hashemite Darqawiya Tariqa into Damascus to the date of the death of its latest contemporary master who was the late Sheihk Shukri Al-Lahfi (may Allah have mercy upon his soul). As the city has all those districts, mosques, hospices, corners, and nooks and all those places that the Tariqa has assigned for its activities like buildings and schools.
Keywords: Islam; İslam; Şazeliyye - Derkaviyye - Haşimiyye - Şam – Şam’da Dini Hayat Shadhili – Damascus -religiousness of Damascus/ Damascene Hashimiya - Darqawi